Autonomous Air and Ground Sensing Systems for Agricultural Optimization and Phenotyping III 2018
DOI: 10.1117/12.2302744
|View full text |Cite
|
Sign up to set email alerts
|

An initial exploration of vicarious and in-scene calibration techniques for small unmanned aircraft systems

Abstract: The use of small unmanned aircraft systems (sUAS) for applications in the field of precision agriculture has demonstrated the need to produce temporally consistent imagery to allow for quantitative comparisons. In order for these aerial images to be used to identify actual changes on the ground, conversion of raw digital count to reflectance, or to an atmospherically normalized space, needs to be carried out. This paper will describe an experiment that compares the use of reflectance calibration panels, for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Current literature on testing its radiometric correction has been limited. We found one study proposed a similar yet simpler approach named At-Altitude Radiance Ratio (AARR), which basically defined the ratio of the DLS and CRP radiance as the correction factor [20]. As shown in Figure 4 of our study, the relationship between DLS and CRP radiance in each band is not a simple ratio; it contains a small yet positive intercept value.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Current literature on testing its radiometric correction has been limited. We found one study proposed a similar yet simpler approach named At-Altitude Radiance Ratio (AARR), which basically defined the ratio of the DLS and CRP radiance as the correction factor [20]. As shown in Figure 4 of our study, the relationship between DLS and CRP radiance in each band is not a simple ratio; it contains a small yet positive intercept value.…”
Section: Discussionmentioning
confidence: 82%
“…The current procedure of RedEdge image correction in common drone data processing packages (e.g., Pix4DMapper) mostly utilizes the CRP panel itself [19]. However, some studies have reported the relatively higher percent errors of its radiometric calibration [15,20]. Our recent practices in a woodland using a RedEdge-M camera [3] also suggested poorly calibrated reflectance, which resulted in overwhelmingly high NDVI of tree canopies.…”
Section: Introductionmentioning
confidence: 99%
“…RSR curves were computed using a method similar to the one described by Mamaghani et al [33]. The RSR determination methodology is shown in Equations (11)–(13).…”
Section: Methodsmentioning
confidence: 99%
“…AARR produces a reflectance image by dividing each spectral band radiance image by the corresponding band-effective downwelling radiance. Equation (27) demonstrates this process [33]. ρi=Ls,iDLSi DLSi=Esolar,iπcos(σ)τi+Lsolar,i where DLSi is the downwelling light sensor radiance recorded by the MicaSense RedEdge, ρi is the reflectance factor, Ls,i is the band effective spectral radiance, Esolar,i is the spectral exoatmospheric solar irradiance, σ is the solar zenith angle, τi is the spectral transmission from space to the sUAS, Lsolar,i is the solar scattered downwelling sky radiance propagating o...…”
Section: Methodsmentioning
confidence: 99%
“…MicaSense proposes a method for conversion of the raw pixel values into absolute spectral radiance values using the onboard Downwelling Light Sensor (DLS) which provides irradiance values for each band (MicaSense, 2017). Mamaghani et al (2018) proposed a new technique making use of the supplied DLS sensor of the MicaSense RedEdge camera, and an improved laboratory method (Mamaghani et al, 2018;Mamaghani and Salvaggio, 2019).…”
Section: Introductionmentioning
confidence: 99%